Numerical and experimental analysis of planar multibody systems with revolute clearance joints - Flores, Paulo (2007)
A comprehensive numerical and experimental study on the dynamic response of a slider-crank mechanism with clearance joints is presented and discussed in this work. The main objective of this study is to provide an experimental verification and validation of the predictive capabilities of the clearance joint models, also proposed in this work. The experimental procedure complements the theoretical or numerical studies in the literature and it provides a proposal for the coherent combination of numerical and experimental work that needs to be undertaken, in order to establish validated models and to identify directions for subsequent studies that will allow for the improvement of the models. This study is supported in an experimental test rig that consists of a slider-crank mechanism with an adjustable radial clearance at the revolute joint between the slider and the connecting rod. The motion of the slider is measured with a linear transducer and an accelerometer. Dynamic tests at different operating crank speeds and with several clearances are performed. The maximum slider acceleration, associated with the impact acceleration, is used as a measure of the impact severity. The results obtained demonstrate the dynamical behavior of a clearance joint and they provide qualitative measures that can be associated with fatigue and wear phenomena, when the system components have to operate with real joints. Furthermore, the correlation between the numerical and experimental results is presented and discussed.